2017
DOI: 10.1007/s00405-017-4519-6
|View full text |Cite
|
Sign up to set email alerts
|

Trismus following different treatment modalities for head and neck cancer: a systematic review of subjective measures

Abstract: The aim of this review was to compare systematically the subjective measure of trismus between different interventions to treat head and neck cancer, particularly those of the oropharynx. Using The Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) Guidelines, Six databases were searched for the text using various terms which include “oropharyngeal/head and neck cancer”, “trismus/mouth opening” and the various treatment modalities. Included in the review were clinical studies (> or =10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…The heterogeneity of the interventions, outcome measures, and populations made it impossible to conduct a meta‐analysis. Loh et al reported no consensus, based on subjective measures, as to which treatment modality had better outcomes …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The heterogeneity of the interventions, outcome measures, and populations made it impossible to conduct a meta‐analysis. Loh et al reported no consensus, based on subjective measures, as to which treatment modality had better outcomes …”
Section: Discussionmentioning
confidence: 99%
“…Loh et al reported no consensus, based on subjective measures, as to which treatment modality had better outcomes. 20 In 2004, only four studies could be included in a systematic review of prevalence of trismus 24 which concluded that RT reduces the mouth opening by 18% at 6-12 months follow-up. We do agree with Dijkstra et al 24 that studies lack consensus on what constitutes trismus.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation induced trismus is a significant cause of treatment related morbidity [25]. The main application of contouring the masticatory apparatus as an avoidance structure is for tumours not infiltrating the muscles in order to spare normal healthy tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse patterns were seen over time regarding perceived difficulties with opening the mouth. Patients' perceptions of difficulties with opening the mouth might be influenced by different factors over time, such as pain, dry mouth, overall emotional functioning, or treatment modalities 81,82 …”
Section: Discussionmentioning
confidence: 99%